Geodiversity Inventory for Geotourism in Tanjung Api Central Sulawesi - DM, abd Rahman; Fitriana, Tati; Botjing, Muslimin U. (Universitas Negeri Gorontalo, 2025)
This study investigates the geological diversity of the Tanjung Api region in Tojo Una-Una Regency, Central Sulawesi, with the aim of identifying potential sites for geotourism and geological heritage designation. Through field observations, lithological and geomorphological mapping, petrographic analysis, and structural interpretation, ten geological sites were inventoried. Among them, Gua Kehidupan and Tanjung Api were identified as fulfilling national criteria for geological heritage due to their exceptional features, including fossil-bearing caves, sinkholes, and active gas seeps related to tectonic brecciation. The remaining sites exhibit significant geotourism value, particularly in coastal, volcanic, and sedimentary contexts. Findings from this study highlight the relevance of geodiversity in supporting sustainable tourism and geoconservation. By integrating geological features with educational and community-based values, Tanjung Api demonstrates strong potential to be developed into a geotourism destination that balances scientific significance, cultural relevance, and ecological preservation. The inventory and qualitative assessment serve as a reference for future geoheritage planning and site management. The study recommends involving local stakeholders in the promotion and conservation of these sites to ensure long-term sustainability and community benefits.